CAR index predicts mortality of hospitalized patients with COVID-19-associated pneumonia - Milić, Nataša (Medical Research, 2024)
Introduction/Aim: COVID-19-associated pneumonia is a serious form of the disease that can result in severe life-threatening complications. This study aims to evaluate the prognostic value of the CAR index in hospitalized patients with COVID-19-associated pneumonia.Material and Methods: This was a single-centre prospective study conducted at the University Clinical Centre Zvezdara during April 2020 among hospitalized patients who were diagnosed with moderate to severe COVID-19-associated pneumonia. The COVID-19 infection was verified by real-time reverse-transcriptase polymerase chain reaction (RT-PCR) test on a sample obtained from a swab of the nasopharynx. The CAR was calculated as CRP and albumin ratio. Results: Two hundred and eight hospitalized patients with COVID-19 associated pneumonia were enrolled. Average age was 54.5±14.6 years, predominantly male (64.4%). Comorbidities were present in 67.3% of patients. The overall in-hospital mortality was 14.4%. CAR index level of 2.0 was identified as the cut-off point for predicting mortality, with sensitivity of 86% and specificity of 72% (AUC=0.844). In univariate regression analysis age, comorbidities, trouble breathing and CAR index were identified as significant predictors of mortality (p
Keywords: CAR index, COVID-19, pneumonia, mortality